Concert-efficient runtime support for concurrent object-oriented programming languages on stock hardware - Karamcheti, V.; Chien, A. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
Inefficient implementations of global namespaces, message passing, and thread scheduling on stock multicomputers have prevented concurrent object-oriented programming (COOP) languages from gaining widespread acceptance. Recognizing that the architectures of stock multicomputers impose a hierarchy of costs for these operations, the authors describe a runtime system which provides different versions of each primitive, exposing performance distinctions for optimization. They confirm the advantages of a cost-hierarchy based runtime system organization by showing a variation of two orders of magnitude in version costs for a CM5 implementation. Frequency measurements based on COOP application programs demonstrate that a 39% invocation cost reduction is feasible by simply selecting cheaper versions of runtime operations.